Fly ash, GGBS, and silica fume based geopolymer concrete with recycled aggregates: Properties and environmental impacts. (16th May 2023) - Singh, Rudra Pratap; Vanapalli, Kumar Raja; Cheela, Venkata Ravi Sankar; Peddireddy, Sreekanth Reddy; Sharma, Hari Bhakta; Mohanty, Bijayananda
Graphical abstract: Highlights: Recycled aggregate (RA) has not shown competent mechanical strength in concrete. The co-effects of flyash (FA), GGBS, and silica fume (SF) on RA based geopolymer concrete were studied. The highest mechanical properties were exhibited with FA: GGBS: SF – 35:50:15. Microstructural analyses showed densification of matrix and C-S-H gel formation. Life cycle analysis results showed 50–60 % reduction in the environmental impacts. Abstract: Recycled coarse aggregates (RA) are sustainable alternatives to natural aggregate (NA) in concrete; however, their mechanical performance has not been competent to the later. The partial replacement of Ordinary Portland Cement (OPC) with the use of industrial by-products for preparation of geopolymer concrete (GPC) has also harnessed great research interest. The objective of the current study is to investigate the technoenvironmental feasibility of using fly ash (FA), ground granulated blast furnace slag (GGBS), and silica fume (SF) in GPC to support the use of 100 % RAs in concrete. This study aims to optimize the proportion of GGBS, FA, and SF in the design mix for the best mechanical performance and eco-efficiency of GPC concrete as compared to conventional OPC concrete. Results indicated positive synergistic effect between FA, GGBS, and SF causing improved mechanical, and microstructural performance of RA based GPCs as compared to OPC concrete with RA. The highest compressive (52.15 MPa), flexural (5.81 MPa), and split tensile strength (5.23 MPa) were exhibited by GPC-MG15 with a cement substitution ratio of FA: GGBS: SF – 35:50:15 which were 18–34 % and 7–10 % higher than that of OPC concrete with NA and RA, compensating the effects of RA addition. The microstructural, and mineralogical properties analysed through SEM and XRD results depicted the densification of the matrix and formation of C-S-H, C-A-S-H, and N-A-S-H gels which could be the possible reasons for the improved performance of GPCs. The environmental performance of optimized GPCs analysed through Life cycle assessment (LCA) reported a 50–60 % reduction in the environmental impacts as compared to OPC concrete with NA. Although GPC-FG50 (GGBS: FA – 50:50) was also environmentally competent, GPC-MG15 was the most sustainable concrete mix which was environmentally superior while not compromising on the functional properties.